Coresiding with parents, son preference, and women's desire for additional children in Vietnam - Yen Thi Hai Nguyen; Truc Ngoc Hoang Dang; Brian Buh; Isabella Buber-Ennser (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2023)
Due to strong filial piety, parents(-in-law) play an important role in their adult daughters' fertility decisions in Vietnam; women feel pressured to fulfil their duties to produce a male descendant for the family. However, rapid urbanisation and industrialisation mean that multigenerational households are becoming less common, despite having been the standard household structure for centuries. Based on the 2020-21 Vietnam Multiple Indicator Cluster Survey, we investigate if women who coreside with the parental generation are more likely to desire additional children. In an industrialised economy, grandparents may be an important source of childcare while simultaneously exerting pressure on their adult children to have additional children. Further, we explore the association of the sex of previous child(ren) to capture the pressure associated with son preference. Multivariate regressions reveal an association between coresiding with parents and the desire for a second child, regardless of the sex of the first child. Among women with two children, third-child desires do not appear to be associated with coresiding with parents but are substantially related to having two daughters. Given the strong two-child norm in Vietnam and previous policies implying negative consequences for parents with three or more children, few women show a desire for a third child. Those women who report a desire for a third child mostly have two daughters, reflecting societal norms about the need for a male heir.
Keywords: 300; Coresiding with parents; Desire for additional children; Son preference; Vietnam Multiple Indicator Cluster Survey